ChemInform Abstract: Synthetic Applications of Intramolecular Thiol‐Ene ′Click′ Reactions. Issue 15 (April 2015) - Scanlan, Eoin M.; Corce, Vincent; Malone, Aoife
Abstract: Review: recent advances in intramolecular thiyl‐radical mediated reactions and their aplications for synthetic and medicinal chemistry; 49 refs.